TRANSITIVITY ANALYSIS OF AFGHAN WOMEN IN ÅSNE SEIERSTAD’S THE BOOKSELLER OF KABUL - Isti'anah, Arina (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2019)
Transitivity analysis is the tool offered by Halliday’s Systemic Functional Grammar (SFG) to observe the writer’s/ speaker’s experience of the real world. In the novel entitled The Bookseller of Kabul, Åsne Seierstad’s description of Afghan women reveals how they are represented in the story. By observing the different characters in the novel, this research focuses on outiling three different woman character roles: wife (Sharifa), mother (Bibi Gul), and daughter (Leila). Stylistic approach focusing on the grammatical features is utilized in this research. The writer’s descriptions of Sharifa, Bibi Gul, and Leila are categorized into the transitivity processes adopting Halliday’s SFG. The analysis shows that different woman roles are represented in similar processes: material, mental, relational, verbal and behavioral. The processes reveal that Afghan women are represented as submissive and devoted characters. Behavioral process is only used to reveal the characters’ being submissive, while material process is employed the most to portray Afghan women’s devotion to the family.